White bird : a Wonder story - Palacio, R. J. (Alfred A. Knopf, 2019)
Tells the story of Julian's Grandmere's childhood when she was hidden by a family in a Nazi-occupied French village because she was Jewish and how a boy that she and her classmates once teased and shunned became her best friend and savior.